2014
DOI: 10.1039/c3cc00173c
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional combinatorial screening enables the bottom-up design of a microRNA-10b inhibitor

Abstract: The RNA motifs that bind guanidinylated kanamycin A (G Kan A) and guanidinylated neomycin B (G Neo B) were identified via two-dimensional combinatorial screening (2DCS). The results of these studies enabled the “bottom-up” design of a small molecule inhibitor of oncogenic microRNA-10b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 24 publications
0
53
0
1
Order By: Relevance
“…This step of the biogenesis process is particularly well-suited for targeting with small molecules thanks to RNA accessibility and some examples of the efficacy of this approach have already been reported in the literature. [14][15][16]18 Furthermore, pre-miRNAs are organized in a three-dimensional structure containing double-stranded regions (stems) and single-stranded regions (bulges and loops) that induce the distortion of RNA double helix thus offering the possibility for small molecules to fix specific binding sites. 30 Concerning the RNA sequences, antibiotics were screened on pre-miR-372 and premiR-373, precursors of two oncogenic miRNAs that are overexpressed in various cancers such as gastric tumors, while they are undetectable in normal cells.…”
Section: Screening Of Antibiotics For Their Ability To Inhibit Oncogementioning
confidence: 99%
See 1 more Smart Citation
“…This step of the biogenesis process is particularly well-suited for targeting with small molecules thanks to RNA accessibility and some examples of the efficacy of this approach have already been reported in the literature. [14][15][16]18 Furthermore, pre-miRNAs are organized in a three-dimensional structure containing double-stranded regions (stems) and single-stranded regions (bulges and loops) that induce the distortion of RNA double helix thus offering the possibility for small molecules to fix specific binding sites. 30 Concerning the RNA sequences, antibiotics were screened on pre-miR-372 and premiR-373, precursors of two oncogenic miRNAs that are overexpressed in various cancers such as gastric tumors, while they are undetectable in normal cells.…”
Section: Screening Of Antibiotics For Their Ability To Inhibit Oncogementioning
confidence: 99%
“…5,[8][9][10] Most of them were discovered after the screening of libraries containing thousands of compounds [11][12][13] or after the evaluation of focused libraries containing fewer compounds known to act as general RNA binders. [14][15][16] Disney and coworkers also described a very efficient lead identification strategy for RNA motif/small molecule interactions, named Inforna, and they applied it to human pre-miRNAs. 17 Recently, we contributed to this field with the first example of focused design of RNA ligands targeting oncogenic pre-miRNAs processing by Dicer.…”
Section: Introductionmentioning
confidence: 96%
“…Our experiments demonstrated that the biological activity is correlated to the inhibition of the production of these oncogenic miRNAs, thus leading to the restoration of normal mRNA transla- This work further demonstrated that it is possible to greatly improve the activity of a minoglycosides by chemical modification. Finally, in the field of the design of specific RNA binders, the works reported by Disney and co-workers represent outstanding and elegant approaches leading to excellent results in terms of specificity and biological activity [64,[73][74]. In fact, this research group developed a lead identification strategy called Inforna [75] allowing for the discovery of highly specific and efficient ligands of pre-miRNAs precursors that are able to inhibit miRNAs biogenesis inside cells.…”
Section: Design Of Mirna Inhibitorsmentioning
confidence: 94%
“…One of the most original approaches toward the discovery of miRNAs inhibitors is the one reported by Disney and co-workers in 2014 [64]. The authors applied a particularly clever screening methodology called 2D combinatorial screening (2DCS) [65][66][67].…”
Section: Focused Screening Approachmentioning
confidence: 99%
See 1 more Smart Citation